Pelatihan Pemanfaatan Limbah Cangkang Kerang Menjadi Kerajinan Hias bagi Pemuda Pesisir di Pantai Tanjung Kota Sorong - Tagor Manurung; Charliany Hetharia; Christania Nadhia Rumengan; Zulfatrin Z; Yuliance Fatie; Abd Jabar Zain Tella (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2026)
Seashell waste is a type of waste commonly found in the Tanjung Beach area, Sorong City. If not utilized properly, this waste can reduce the cleanliness of the coastal environment. This community service activity aims to provide training to coastal youth on utilizing seashell waste into decorative crafts. The methods used in this activity include socialization, demonstration, and hands-on practice in making decorative crafts from seashell materials. The activity was carried out by involving coastal youth as training participants. The results of the activity show that participants were able to understand the stages of seashell processing and produce decorative crafts from materials that were previously not optimally utilized. In addition to improving participants' skills, this activity also provided insights regarding the utilization of waste as useful craft materials. Thus, the training conducted can be one of the efforts to develop the creativity of coastal youth through the utilization of seashell waste in the Tanjung Beach area, Sorong City.